Educational program for middle-level public health nurses to develop new health services regarding community health needs: protocol for a randomized controlled trial - Yoshioka-Maeda, Kyoko (BMC Nurs, 2018)
BACKGROUND: Developing health services is a key strategy for improving the community health provided by public health nurses. However, an effective educational program for improving their skills in planning such services has not been developed. To describe our program and its evaluation protocol for the education of middle-level public health nurses to improve their skills in developing new health services to fulfil community health needs in Japan. METHODS: In this randomized control trial, eligible participants in Japan will be randomly allocated to an intervention group and a control wait-list group. We will provide 8 modules of web-based learning for public health nurses from July to October 2018. To ensure fairness of educational opportunity, the wait-list group will participate in the same program as the intervention group after collection of follow-up data of the intervention group. The primary outcomes will be evaluated using the scale of competency measurement of creativity for public health nurses at baseline, immediately after the intervention. Secondary outcomes will be knowledge and performance regarding program development of public health nurses. DISCUSSION: This study will enable the analysis of the effects of the educational program on public health nurses for improving their competency to develop new health services for fulfilling community health needs and enriching health care systems. TRIAL REGISTRATION: We registered our study protocol to the University hospital Medical Information Network- Clinical Trials Registry approved by International Committee of Medical Journal Editors (No. UMIN000032176, April, 2018).